THE SIGNIFICANCE OF FELDMAN METHOD IN ART CRITICISM AND ART EDUCATION - Alashari, Duaa (International Journal of Psychosocial Rehabilitation, 2024)
This paper addresses art criticism, which undoubtedly plays a significant role in enriching the art’s creative and aesthetic state. The paper aims to identify the steps of art criticism for the Feldman. Feldman developed a four steps method to be able to interpret, judge and evaluate artistic works. The researcher has carried out this study by focusing on artistic criticism basics to help guide students to improve and develop their level regarding artistic criticism. The method used in this study is descriptive and analytical. The study reached several conclusions, among which was that art criticism is an organized series of situations. Feldman method is a process that requires an in-depth analysis of art issues, understanding the various critical trends, being aware of all artistic developments, artistic achievements, and being aware of the principles and elements of art. The relevance of criticism to art is closely related because criticism is centred around the work of art, and stems from analysis and distinction.